2017
DOI: 10.3389/fphar.2017.00357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of JNJ-54717793 a Novel Brain Penetrant Selective Orexin 1 Receptor Antagonist in Two Rat Models of Panic Attack Provocation

Abstract: Orexin neurons originating in the perifornical and lateral hypothalamic area are highly reactive to anxiogenic stimuli and have strong projections to anxiety and panic-associated circuitry. Recent studies support a role for the orexin system and in particular the orexin 1 receptor (OX1R) in coordinating an integrative stress response. However, no selective OX1R antagonist has been systematically tested in two preclinical models of using panicogenic stimuli that induce panic attack in the majority of people wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 81 publications
4
51
0
Order By: Relevance
“…The efficacy observed in the rat CO 2 challenge is unlikely to be driven by nonspecific effects, as demonstrated by the lack of effect on baseline locomotor or autonomic activity, and by the lack of effect of the less active enantiomer JNJ-63821238. A high level of target engagement (>90%) was required to demonstrate efficacy in the CO 2 challenge, as previously observed with other OX1R antagonists (SB-334867, Compound 56 and JNJ-54717793) 11,12,28 . These findings are consistent with the hypothesized role of OX1R signaling in the mechanism underlying CO 2 challenge-induced fear, as exposing rats to higher concentration of CO 2 depolarizes orexin neurons by interacting with pH/CO 2 -chemosensitive K + channels 29 .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The efficacy observed in the rat CO 2 challenge is unlikely to be driven by nonspecific effects, as demonstrated by the lack of effect on baseline locomotor or autonomic activity, and by the lack of effect of the less active enantiomer JNJ-63821238. A high level of target engagement (>90%) was required to demonstrate efficacy in the CO 2 challenge, as previously observed with other OX1R antagonists (SB-334867, Compound 56 and JNJ-54717793) 11,12,28 . These findings are consistent with the hypothesized role of OX1R signaling in the mechanism underlying CO 2 challenge-induced fear, as exposing rats to higher concentration of CO 2 depolarizes orexin neurons by interacting with pH/CO 2 -chemosensitive K + channels 29 .…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, OX1Rs are more selectively expressed in bed nucleus of the stria terminalis, amygdala, cingulate cortex, and the noradrenergic neurons of the locus coeruleus 8 . Consistent with the anatomical distribution of OX1R, a critical role for this receptor is emerging in complex emotional behavior, such as association of OX1R pathway overactivation with panic or anxiety states [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…For example, in rodent models of panic, an extreme form of anxiety, animals with panic vulnerability treated with the OX 1 R antagonist compound 56 reduced panic-like behaviors in a sodium lactate model of panic induction 88 . Similarly, treatment with the OX 1 R antagonist JNJ-54717793 attenuates panic-like behavior and cardiovascular responses in both the sodium lactate model of panic and a carbon dioxide (CO 2 ) model of panic provocation 89 . Additional studies within the CO 2 model that screened selective Hcrt receptor antagonists (SORAs) and dual Hcrt receptor antagonists (DORAs) found that both a SORA1 (compound 56) and a DORA-12 attenuate anxiety-like behaviors but that a SORA2 did not 90 .…”
Section: Part Ii: Affect and Motivationmentioning
confidence: 99%